PELAKSANAAN CITIZEN DIPLOMACY SEBAGAI UPAYA PENGUATAN IDENTITAS BANGSA di ERA ASEAN COMMUNITY - Setyasih Harini & Halifa Haqqi (Universitas Slamet Riyadi, 2017)
The Regional international relation recently has been the other trend onglobal politic. ASEAN as a regional organization couldn’t apart from challengeof global politic-economy. One effort to face globalization by the increasingparticipation of public through citizen diplomacy. Coomunication technologycould wider opportunities of citizen to make relation with another. Relationship ofculture among citizen of many countries could support diplomacy of govenment. Italso strengthen national identity. Question research: how did implementation ofcitizen diplomacy could strengthen national identity in ASEAN Community?Purpose of this research to explain implementation of citizen diplomacy couldstrengthen national identity in ASEAN Community. As a qualitative research, datawas collected from literature. Data analysis with data reduction, data display andverification. Object research about implementation of citizen diplomacyof culturecould strengthen national identity in ASEAN Community. Result of this researchthat implementation of citizen diplomacy of culture could support governmentdiplomacy and strengthen national identity in ASEAN Community.Key words: citizen diplomacy, culture, ASEAN Community